Identification and characterization of coleoptera‑specific vip and cry genes in Bacillus thuringiensis isolates - Alves, Meire de Cássia; Rossi, Juliana Regina; Rodrigues, Maria Gabriela Fontanetti; Alves, Eliane Cristina da Cunha; Ferraudo, Antonio Sergio; Lemos, Manoel Victor Franco; Desidério, Janete Apparecida; Fernandes, Odair Aparecido (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to identify and characterize cry3, vip1, vip2 and vip1/vip2 genes in a collection of 1,078 Bacillus thuringiensis isolates potentially toxic against Coleoptera larvae. Pairs of primers derived from conserved regions of genes and from sequence alignment consensus were used. Subsequently, positive isolates were characterized by PCR‑RFLP, using specific restriction enzymes to identify new subclasses of genes in the isolates. One hundred and fifty‑one isolates were positive for the evaluated genes, with higher frequency for the vip1/vip2 gene (139 isolates). By PCR‑RFLP, 14 polymorphic profiles were observed, indicating the presence of different alleles, and, therefore, of distinct subclasses of these genes.